What Counts as Evidence in the Understanding of School Exclusion in England? - Daniels, Harry; Porter, Jill; Thompson, Ian (Frontiers in Education, 2022)
Exclusion from school can be regarded as a seemingly simple but in fact a rather complex intervention in response to the ‘wicked problem’ of behaviour in schools (Armstrong, 2018). This paper will discuss what counts as evidence that may used to inform policy and judgements on practices of exclusion. The role of evidence, and how this is measured, has long been an issue of contention in educational research. This is particularly true for research that focuses on educational inequality and inclusion or exclusion. In this paper we will discuss issues concerning evidence with respect to two aspects of exclusion in England. Firstly, we will focus on questions concerning the scale of the problem, examining both the statistical evidence of official exclusions and data concerning the myriad of ways in which children may experience other forms of exclusion. Taken together, this indicates an under-estimate of the numbers of young people missing an education. We then move to a consideration of the evaluation of means of reducing exclusion, arguing for a shift from an individual to a systemic in context account that recognizes the role of cultural transmission and cultural historical theory.